Aktivitas Antioksidan dan Antidiabetes In Vitro Ekstrak Air Kulit Batang Kayu Manis (Cinnamomum burmannii) Asal Kota Jambi: In Vitro Antioxidant and Antidiabetic Activities of Aqueous Extract of Cinnamon Bark (Cinnamomum burmannii) from Jambi - Maulana, Farhan; Safithri, Mega; Safira P, Ukhradiya Magharaniq (Departemen Biologi, Institut Pertanian Bogor, 2022)
Cinnamon (Cinnamomum burmannii) is an herbal plant that has a function, one of which is lowering glucose in the blood and warding off free radicals that cause oxidative stress. This study aims to determine the inhibitory activity of the enzyme compound α-glucosidase and the suppression of DPPH free radicals using the first, second, and third replications of cinnamon bark water extract (C. burmannii) as a natural source of antidiabetic drug candidates. The extraction method uses the infundation technique and is carried out using a spectronometer. The highest yield was obtained in the extraction of the first repeat, which is with an average of 0.674%, the yield did not differ markedly (p>0.05) with the second and third repeats. The highest results of total phenolic testing were obtained in the second repeat extraction of 100.374 GAE g-1, the results differed markedly (p<0.05) with the first and third repeats. The highest results of testing antioxidant activity were obtained at the extraction of the first repeat which was 9.012 mg of AAE g-1, the results differed markedly (p<0.05) with the second and third repeats. The highest result of testing of enzyme inhibition activity α-glucosidase was found in the extraction of the first repeat which was 99.650%, the results did not differ markedly (p>0.05) with the second and third repeats.